2018
DOI: 10.2147/ott.s146228
|View full text |Cite
|
Sign up to set email alerts
|

MCL-1 inhibition in cancer treatment

Abstract: Myeloid cell leukemia-1 (MCL-1), a member of antiapoptotic BCL-2 family proteins, is a key regulator of mitochondrial homeostasis. Frequent overexpression of MCL-1 in human primary and drug-resistant cancer cells makes it an attractive cancer therapeutic target. Significant progress has been made in the development of small-molecule MCL-1 inhibitors in recent years, and three MCL-1 selective inhibitors have advanced to clinical trials. This review briefly discusses recent advances in the development of small m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 91 publications
(105 reference statements)
3
88
0
1
Order By: Relevance
“…Taken together, compounds with potent activity for eliminating Bcl-2 or Mcl-1 in cancer cells are of great interest as good candidates for targeted therapy. In agreement with the use of Mcl-1 as a target for cancer therapy [11], our previous study highly supported this concept, where in our experiments, the treatment of RT in an NSCLC cell line (H460) resulted in apoptotic cell death through an Mcl-1 proteasomal degraded mechanism [23]. In the same way, not only in a known lung cancer cell line, but we also proved that the absence of Mcl-1 after RT treatment in primary lung cancer cell lines derived from patients (Figure 3a,b) could trigger the apoptotic pathway, which led to the death of cancer cells (Figure 1f,g).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Taken together, compounds with potent activity for eliminating Bcl-2 or Mcl-1 in cancer cells are of great interest as good candidates for targeted therapy. In agreement with the use of Mcl-1 as a target for cancer therapy [11], our previous study highly supported this concept, where in our experiments, the treatment of RT in an NSCLC cell line (H460) resulted in apoptotic cell death through an Mcl-1 proteasomal degraded mechanism [23]. In the same way, not only in a known lung cancer cell line, but we also proved that the absence of Mcl-1 after RT treatment in primary lung cancer cell lines derived from patients (Figure 3a,b) could trigger the apoptotic pathway, which led to the death of cancer cells (Figure 1f,g).…”
Section: Discussionsupporting
confidence: 62%
“…Recent evidence has suggested that the ability to evade apoptosis, survival during metastasis, and resistance to therapy are likely to be dependent on the expression and function of the pro-survival Bcl-2 proteins [8]. Consequently, it is not unexpected that the amplification and overexpression of pro-survival Bcl-2 proteins, such as Bcl-2 and Mcl-1, are found in many cancer types (e.g., non-small-cell lung cancer, breast cancer, ovarian cancer, prostate cancer, and pancreatic cancer) [9][10][11]. Bcl-2 family members, like Bcl-2 and Mcl-1, have been shown to dominate negative regulation for apoptosis control and to be responsible for chemotherapeutic resistance [12].…”
Section: Introductionmentioning
confidence: 99%
“…Using RT-qPCR, the authors of the current study revealed that MYB may improve cell proliferation by enhancing cell cycle progression through CCND1 upregulation and p21 downregulation. Additionally, MYB may decrease apoptosis by upregulating MCL1 expression, which encodes proteins belonging to the Bcl-2 family (34).…”
Section: Discussionmentioning
confidence: 99%
“…Significant changes were identified in five of the 22 genes (data not shown). The expression of CCND1 and MCL1, which are associated with cell proliferation (33,34), was upregulated following MYB overexpression, whereas p21 expression was downregulated (Fig. 5A).…”
Section: Myb Promotes Sacc Lung Metastasis In Vivomentioning
confidence: 99%
“…AT-101 has been administered in combination with ABT-737 representing the first small molecule with anti MCL-1 activity investigated in clinical trials [109]. Additionally, a number of MCL-1 targeting compounds (MIK665, S64315, AMG176, AZD5991) have entered phase I clinical trials as a single agent for lymphoma, myeloma and hematologic malignancies [116].…”
Section: Treatment Approaches Targeting the Anti-apoptotic Bcl-2 Famimentioning
confidence: 99%